Vers une édition électronique de la glose d’Oxford - Emmanuelle Kuhry (Humanités Numériques)
The present paper describes a project aiming at editing University glosses of the thirteenth century copied around the Aristotelian treatises on nature. No reference edition of this corpus has been carried out. Furthermore, editions of glosses in paper or electronic form do not always meet the reader’s needs, among which the rendition of complex manuscript traditions and of the link between the glosses and the text, or a simplified interface for reading the text and the marginal and interlinear glosses sequentially. XML-TEI encoding allows to render these features and to produce outputs to paper and electronic formats, thanks to XSLT transformation sheets. The electronic format enables the editions of ancient sources to be read in new ways. Through the creation of encoding and transforming tools and methodologies, the project seeks the constitution of a resource center for scientific edition.